2017
DOI: 10.1016/j.ssmph.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a scale of neighbourhood informal social control relevant to pre-schoolers’ physical activity: A cross-sectional study

Abstract: Childhood physical activity (PA) is important for health across the lifespan. Time pre-schoolers spend outdoors, which has been associated with more PA, is likely influenced by parents’ perception of neighbourhood informal social control relevant to pre-schoolers' PA, defined as the willingness of neighbours to intervene to ensure social order and a safe community environment for young children's active play. To advance measurement of this construct, we assessed factorial and construct validities of the PA-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Studies conducted in the USA, Western Europe, and Eastern Europe have demonstrated that informal social control was associated with higher self-perceived health and PA. 23 , 39 , 42 A Japanese study indicated that informal social control promoted neighborhood safety by preventing juvenile delinquency and was associated with outdoor PA. 18 Moreover, neighborhood informal social control can affect parents' perceptions of safety and allow them to encourage their youth to be physically active outdoors. 43 A Dutch study noted that correcting deviant behaviors in an early stage of childhood development may be related directly to adolescents refraining from acting up badly and indirectly by providing them with self-confidence. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the USA, Western Europe, and Eastern Europe have demonstrated that informal social control was associated with higher self-perceived health and PA. 23 , 39 , 42 A Japanese study indicated that informal social control promoted neighborhood safety by preventing juvenile delinquency and was associated with outdoor PA. 18 Moreover, neighborhood informal social control can affect parents' perceptions of safety and allow them to encourage their youth to be physically active outdoors. 43 A Dutch study noted that correcting deviant behaviors in an early stage of childhood development may be related directly to adolescents refraining from acting up badly and indirectly by providing them with self-confidence. 44 …”
Section: Discussionmentioning
confidence: 99%
“…Low and high walkable neighbourhoods were those with a walkability index falling in the first and fourth quartiles, respectively. This strategy has been often employed in studies on the neighbourhood environment to maximise variation in types of environments [2325]. Census data were used to classify neighbourhoods into those with a medium percentage of Chinese dwellers (5–10% of residents were Chinese) or high percentage of Chinese dwellers (> 10% of residents were Chinese).…”
Section: Methodsmentioning
confidence: 99%
“…Scales measuring the PA-related social environment have also been developed and validated among children in Hong Kong. For example, the PA-related Neighborhood Informal Social Control Scale for Parents of Preschoolers (PANISC-PP) was developed [ 48 ], with satisfactory factorial and construct validities and internal reliabilities further established [ 49 ]. Furthermore, parent-report measures of home and neighborhood environmental correlates of PA for preschool-aged children in Hong Kong was also developed with satisfactory internal consistency reliabilities and test-retest reliabilities [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PA measures [ 43 , 44 , 45 , 46 ] provided valid tools for collecting self-report data on Hong Kong children’s PA for both correlational and interventional studies. Validating the observational tool for measuring PA among Hong Kong children [ 47 ], the PA-related home and neighborhood measures [ 48 , 49 , 50 ] are also very important which provided various approaches for collecting different types of PA data. The measures of PA-related psychological [ 51 , 52 , 53 ] can be used for exploring the psychological benefits and the potential changing mechanisms of PA interventions.…”
Section: Discussionmentioning
confidence: 99%